Подготовка научных кадров менеджеров и экономистов в Крымском регионе - Подсолонко, В.А. (Кримський науковий центр НАН України і МОН України, 2005)
Дается обоснование необходимости расширения подготовки аспирантов в Украине и Крыму. Описывается опыт повышения целеопределенности и усиления структурирования процессов написания и аттестации диссертационных работ. Приводятся примеры усиления специализации комиссий и их членов в специализированном Ученом совете по защите кандидатских диссертаций. Показаны примеры экспертизы диссертаций на соискание научной степени кандидата экономических наук. Дається обгрунтування необхіднмості поширення підготовки аспирантів в Україні і Криму. Описується досвід підвищення цілевизначеності та посилення структурування процесів написання та атестації дисертаційних робіт. Наведено приклади посилення спеціалізації комісій та їх членів в спеціалізованій Вченій Раді по захисту кандидатських дисертацій. Показано приклади експертизи дисертацій на здобуття наукового ступеня кандидата економічних наук. The substantiation of necessity of expansion of preparation of the post-graduate students in Ukraine and Crimea is given. The experience of increase of a role of definition of the purpose and strengthening of processes structurization of a spelling and certification of the dissertations is described. The examples of strengthening of specialization of commissions and their members in the specialized scientific council on protection of the candidate dissertations are resulted. The examples of examination of the dissertations on competition of a scientific degree of the candidate of economic sciences are shown.